KOMUNIKASI VISUAL DALAM STRATEGI MITIGASI BENCANA: EFEKTIVITAS MEDIA INFOGRAFIS SEBAGAI UPAYA PENGURANGAN RESIKO BENCANA - Ulhaq, Muhammad Zia; Wulandari, Sri Reski (KAGANGA KOMUNIKA: Journal of Communication Science, 2025)
Indonesia is a country with a high level of disaster vulnerability, making it necessary to develop communication strategies that can reach the wider public quickly and be easily understood. The purpose of this study is to analyze the effectiveness of visual communication design in disaster mitigation education, with a focus on the use of infographics as the primary medium for delivering information. This research employs a qualitative method with a literature review approach, gathering data from scientific journals, books, official reports from institutions such as BNPB and BMKG, as well as visual documentation of disaster-related infographics. The analysis was conducted through literature classification and thematic analysis to identify design patterns proven effective in conveying mitigation messages. The findings indicate that the effectiveness of infographics is determined by three key aspects: message clarity, visual readability, and cultural relevance. Visual elements such as contrasting colors, universal icons, hierarchical layouts, and culturally adapted symbols have been shown to enhance public understanding, information retention, and disaster preparedness. This study provides a foundation for developing more inclusive, adaptive, and evidence-based visual communication strategies for disaster mitigation.   .Keywords: Visual Communication, Disaster Mitigation, Literature Study, Infographics, Design Communication